2019
DOI: 10.3847/1538-4357/ab4252
|View full text |Cite
|
Sign up to set email alerts
|

Gas and Dust Temperature in Prestellar Cores Revisited: New Limits on Cosmic-Ray Ionization Rate

Abstract: We develop a self-consistent model for the equilibrium gas temperature and size-dependent dust temperature in cold, dense pre-stellar cores, assuming an arbitrary power-law size distribution of dust grains. Compact analytical expressions applicable to a broad range of physical parameters are derived and compared with predictions of the commonly used standard model. It is suggested that combining the theoretical results with observations should allow us to constrain the degree of dust evolution and the cosmic-r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 57 publications
6
43
0
Order By: Relevance
“…The CRIR moves to lower (higher) values with peaks around 3×10 −17 s −1 . Overall, our estimated CRIR obtained from an unconstrained and a model-independent approach, is close to typical values reported by van der Tak & van Dishoeck (2000) 4 but far from the value of ζ 2 ∼ 10 −16 s −1 measured in diffuse clouds and recently reported by Ivlev et al (2019) for the same pre-stellar core. Thus, chemistry appears to favor lower values of ζ 2 in dense cores 5 .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The CRIR moves to lower (higher) values with peaks around 3×10 −17 s −1 . Overall, our estimated CRIR obtained from an unconstrained and a model-independent approach, is close to typical values reported by van der Tak & van Dishoeck (2000) 4 but far from the value of ζ 2 ∼ 10 −16 s −1 measured in diffuse clouds and recently reported by Ivlev et al (2019) for the same pre-stellar core. Thus, chemistry appears to favor lower values of ζ 2 in dense cores 5 .…”
Section: Resultssupporting
confidence: 89%
“…A pure theoretical method based on dust temperature evaluation has been proposed and applied to L1544 by Ivlev et al (2019). The latter provided an estimate of the CRIR of ζ 2 ∼ 10 −16 s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Second, the cosmic ray ionization rate is around´--3 10 s 16 1 , namely slightly (a factor of two) lower than that used in previous studies. This may mean that it slightly decreases going outward from the central object from which the outflow/jets emanate, which is consistent with the hypothesis that cosmic rays, like particles, are accelerated by the dense shocks at the jet base (Padovani et al 2016;Ivlev et al 2019).…”
Section: Chemical Modelingsupporting
confidence: 83%
“…Some implications of this work 7.1. Gas temperature Ivlev et al (2019) has shown that in the core center the gas temperature is sensitive to the dust grain-size distribution. At these densities, the gas heating is dominated by CRs, which heat the gas at a rate proportional to the ionization rate, and is only weakly dependent on other parameters (Glassgold et al 2012).…”
Section: Grain Fragmentationmentioning
confidence: 99%